Pengaruh pengetahuan guru dan kualitas guru terhadap kualitas sekolah dengan kinerja guru sebagai variabel intervening - Lesmanawati, Atun; Nuryanto, Uli Wildan; Handayani, Yola Sukma (Universitas Muhammadiyah Magelang, 2024)
This study aims to determine the effect of teacher knowledge on teacher performance, teacher quality on teacher performance, teacher knowledge on school quality, teacher quality on school quality, teacher performance on school quality, and teacher knowledge and teacher quality on school quality through teacher performance. The study was conducted in 28 private primary schools in Serang Regency, which focused on 435 teachers and obtained a sample size of 208 teachers by determining the sample size using Slovin's formula. The analysis method in this study uses descriptive index numbers and SEM PLS as an inferential analysis. SEM PLS analysis was performed using External analysis model and Internal analysis model and followed by Hypothesis Testing on 7 research hypotheses. The results of the study show that seven hypotheses are accepted, that is, teacher knowledge has a significant effect on teacher performance and school quality, teacher quality on teacher performance and school quality, teacher performance on school quality and school quality. teacher knowledge and teacher quality have a significant impact on school quality through teacher performance.